EXPLORATORY STUDY TO ASSESS THE EFFICACY OF JALAUKAVACHARANA (HIRUDOTHERAPY) IN THE MANAGEMENT OF VICHARCHIKA (ECZEMA) - Prakash, Abhay; Raj GR, Arun; Debnath, Parikshit; Prasad, Lalta; Prakash, Sanjeev (International Journal of Ayurveda and Pharma Research, 2015)
Though the skin diseases are not a life threatening, they make the patient worried due to its appearance. Severe itching or burning or oozing disturbs his routine and its nature susceptible to be chronic. Even though many skin diseases may be cured yet the relapsing nature of few diseases (eczema, psoriasis, seborricdermatitis etc.) makes it much harassment for patients and trouble some for physician too. Eczema is a pattern of inflammatory response of the skin characterized by redness, skin edema, itching and dryness, with possible crusting, flaking, blistering, cracking, oozing or bleeding. Ayurvedic science explains this disease as Vicharchika. As the Ayurveda classics have detailed the use of Jalauka (leech) in the treatment of various skin manifestations, the present study has been performed to assess the effectiveness of blood-letting by making use of leech in the management of Eczema. By the study, making use of leeches has found to be very effective in reliving the signs and symptoms of Eczema.